Quantifying the efficacy of retrofitting slabs under local blast loads through numerical analysis using polyurea-infused woven glass fiber mesh composites / Muhammad Nuzulul Furqan, Sofia W Alisjahbana and Muhammad Daffa Fachrur Reza - Furqan, Muhammad Nuzulul; W Alisjahbana, Sofia; Muhammad Daffa Fachrur Reza, Muhammad Daffa Fachrur Reza (2024)
Terrorists now frequently use explosive attacks to carry out assaults. They frequently utilize car bombs, luggage bombs, or suicide bombs to target key buildings, creating fear and drawing public attention. The specimens used consist of semi-rigid slabs with varying thicknesses of 15 cm, 18 cm, and 20 cm. Two models were considered: one with additional reinforcement using polyurea-infused woven glass fiber mesh composites and another without any additional reinforcement. These slabs were subjected to blast loads. Numerical analysis was conducted using Wolfram Mathematica software. When polyurea-infused woven glass fiber mesh composites were used as reinforcement, slabs of decreasing thickness showed a big rise in their resistance to blast loads. This demonstrates the effectiveness of this material in enhancing slab performance under blast conditions. For example, when extra retrofitting using polyurea-infused woven glass fiber mesh composites was done at the same thickness (15 cm), a big drop was seen—a drop of 97.61%. Similarly, at a thickness of 18 cm, a decrease of 30.48% was experienced, while at a thickness of 20 cm, the reduction reached 70.40%.